Necrose Etendue De Lâ€™estomac Sur Dilatation Gastrique Chez Un Patient Suivi Pour Tumeur Cerebelleuse - Rakotomena, DavidÃ S.; Rakotondrainibe, AurÃ©lia; Andrianah, Gabrielle E.P.; Rajaonera, Tovohery A.; Rakoto-Ratsimba, Hery N. (European Scientific Journal, ESJ, 2018)
Acute necrosis with a gastric dilatation is very rare. It usually occurs on psychiatric and neurological field. The preoperative diagnosis is difficult, and it is often revealed by radiological exams. With or without surgery, mortality remains high. We report a case of gastric necrosis in a patient with a severe neurological history. The clinical signs were vomiting, without intestinal transit disorders, and poor general condition. The radiological exams revealed gastric gas gangrene in the stomach wall. The surgical management determined the limit of gastric necrosis and gastrectomy was performed.